2014
DOI: 10.20489/intjecse.107931
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of Modified Turkish Version of Autism Behavior Checklist (ABC): Results of Pilot Study

Abstract: The purpose of this pilot study is to investigate reliability and validity of Modified Turkish

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Thirdly, no golden standard diagnostic tools or interviews were used for diagnoses or research reliability, mainly because the golden standard diagnostic tools for ASD, Autism Diagnostic Observation Schedule-second Edition (ADOS-2; Lord et al, 2012) and/or the Autism Diagnostic Interview-Revised (ADI-R; Lord et al, 1994), haven’t been translated or adapted to the Chinese language, or widely used in China, and no golden standard diagnostic tools have been established for ADHD. Lastly, although the ABC scale is a widely recognized tool for assessing ASD symptoms (e.g., Fumagalli Marteleto & Marcondes Pedromônico, 2005; Sun et al, 2013; Tang et al, 2023) with demonstrated reliability and construct validity (e.g., Eaves et al, 2000; Eaves & Williams, 2006; Juneja et al, 2010; Ozdemir et al, 2013; Yousefi et al, 2015), it was developed based on the DSM-III criteria (Krug et al, 1980). Future studies should consider incorporating more updated scales that align with the DSM-5 criteria and more recent conceptualizations of ASD (e.g., Modified Checklist for Autism in Toddlers Revised [MCHAT-R/F]; Robins et al, 2014) to assess ASD symptoms, especially language-related ASD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, no golden standard diagnostic tools or interviews were used for diagnoses or research reliability, mainly because the golden standard diagnostic tools for ASD, Autism Diagnostic Observation Schedule-second Edition (ADOS-2; Lord et al, 2012) and/or the Autism Diagnostic Interview-Revised (ADI-R; Lord et al, 1994), haven’t been translated or adapted to the Chinese language, or widely used in China, and no golden standard diagnostic tools have been established for ADHD. Lastly, although the ABC scale is a widely recognized tool for assessing ASD symptoms (e.g., Fumagalli Marteleto & Marcondes Pedromônico, 2005; Sun et al, 2013; Tang et al, 2023) with demonstrated reliability and construct validity (e.g., Eaves et al, 2000; Eaves & Williams, 2006; Juneja et al, 2010; Ozdemir et al, 2013; Yousefi et al, 2015), it was developed based on the DSM-III criteria (Krug et al, 1980). Future studies should consider incorporating more updated scales that align with the DSM-5 criteria and more recent conceptualizations of ASD (e.g., Modified Checklist for Autism in Toddlers Revised [MCHAT-R/F]; Robins et al, 2014) to assess ASD symptoms, especially language-related ASD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Psychiatric diagnoses of the patients were based on DSM-5 criteria using clinician’s opinion and supportive assessment tools. For example, these assessment tools included the Modified Checklist for Autism in Toddlers (M-CHAT) in ASD scanning in toddlers, the Autism Behavior Checklist (ABC) in different forms and level of severity of ASD, Turgay’s ADHD Evaluation Scale for ADHD, the Specific Learning Difficulties Symptom Scale for SLD, the State-Trait Anxiety Inventory (STAI) for anxiety disorders, and the Beck Depression Inventory (BDI) for depressive disorders [6,16,17,18,19,20,21]. The study protocol was approved by Trakya University Scientific Research Ethics Committee dated 05/11/2018 and numbered TUTF-BAEK 2018/381.…”
Section: Methodsmentioning
confidence: 99%
“…Mental disability along with autistic features presented that the child had no preconception of consequences of his behavior. On the Modified Turkish Version of Autism Behavior Checklist (ABC) [ 11 ], the child's score was 42, indicating a clinical condition of low-functioning autism.…”
Section: Case Reportmentioning
confidence: 99%